Correlation of ultrasound imaging with histopathological findings in gestational trophoblastic disease (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Gestational trophoblastic diseases include a spectrum of pregnancy-related diseases caused by abnormal proliferation of the placenta.  The main aim of this study was to correlate ultrasound imaging with histopathological findings.Method: This is the retrospective chart review of findings of transabdominal ultrasonography in clinically suspected gestational trophoblastic diseases which were confirmed by histopathology after the evacuation of a product of conception during 3 years from 2016 to 2019 at Patan Hospital, Patan Academy of Health Sciences Nepal. The accuracy of sonography was correlated with histopathological findings and analyzed by Fisher’s Exact or Pearson’s Chi-square tests. The study was approved ethically.Result:  Among 155 clinically suspected gestational trophoblastic diseases, ultrasonography was accurate in 141(91.0%) and confirmed by histopathology; 14(9.0%) were non-molar miscarriages. In 141 histologically confirmed trophoblastic disease, 110(71.0 %) were partial mole, 15(9.7%) complete mole, 12(7.7%) invasive mole and 3(1.9 %) persistent mole, and 1(0.6%) choriocarcinoma. Snowstorm appearance and absence of fetus were statistically significant ultrasonography findings.Conclusion:  The ultrasound is a reliable non-invasive first-line imaging modality for the diagnosis of gestational trophoblastic diseases and had an accuracy of 91% as confirmed by histopathology in this study.